Experimental Demonstration of Single-Channel EEG Signal Using 32 × 32 Pixel OLED Screen and Camera - Aggarwal, Geetika; Dai, Xuewu; Saatchi, Reza; Binns, Richard; Sikandar, Ajay (Electronics (Basel), 2019)
Currently, the radiofrequency (RF)-based wireless technology deployed in electroencephalography (EEG) to diagnose brain diseases suffers from frequency spectrum and electromagnetic interference, and might also have adverse effects on the health of patients and equipment used in hospitals, especially in RF-restricted zones like intensive care units (ICUs). Optical wireless communication (OWC), specifically visible light communication (VLC), is featured in 5G network to complement the radiofrequency (RF) technologies due to the fact that huge unlicensed bandwidth and available infrastructure, both indoor and outdoor, reduces the implementation cost. The conventional VLC systems deploy photodiodes as receivers, requiring hardware and infrastructure modifications in addition to smaller field of view (FOV), but the use of cameras reduce the infrastructure cost due to inbuilt filters and a wider FOV coverage gives the ability to scale a larger area. The wider FOV and the movement of camera rotation, without any additional adjustments to maintain the line-of-sight (LOS), allows the patient to be anywhere within the room and FOV. This paper demonstrates a novel healthcare system for EEG using visible light optical camera communication (VL-OCC), where a 32 × 32 pixel OLED screen acts as transmitter and the receiver section consists of several different cameras such as digital single-lens reflex camera (DLSR), android smartphone, and Thorlabs camera. The experiments were performed in LOS deploying on-off keying (OOK) modulation at several distant measurements to determine the system reliability and stability through bit error rate (BER) performance. The proposed system results depict that the DSLR camera outperforms the smartphone and Thorlabs cameras, as it is capable of transmitting an error free bit rate of 2.8 kbps at 30 fps up to 5.5 m.